Infection With the US Neisseria meningitidis Urethritis Clade Does Not Lower Future Risk of Urethral Gonorrhea. (20th September 2021) - Turner, Abigail Norris; Carter, Alexandria M; Tzeng, Yih-Ling; Stephens, David S; Brown, Morgan A; Snyder, Brandon M; Retchless, Adam C; Wang, Xin; Bazan, Jose A
Abstract: Background: Cross-protective immunity between Neisseria meningitidis (Nm) and Neisseria gonorrhoeae (Ng) may inform gonococcal vaccine development. Meningococcal serogroup B (MenB) outer membrane vesicle (OMV) vaccines confer modest protection against gonorrhea. However, whether urethral Nm infection protects against gonorrhea is unknown. We examined gonorrhea risk among men with US Nm urethritis clade (US_NmUC) infections. Methods: We conducted a retrospective cohort study of men with urethral US_NmUC (n = 128) between January 2015 and April 2018. Using diagnosis date as the baseline visit, we examined Ng status at return visits to compute urethral Ng risk. We compared these data to 3 referent populations: men with urethral Ng (n = 253), urethral chlamydia (Ct) (n = 251), and no urethral Ng or Ct (n = 255). We conducted sensitivity analyses to assess varied approaches to censoring, missing data, and anatomical site of infection. We also compared sequences of protein antigens in the OMV-based MenB-4C vaccine, US_NmUC, and Ng. Results: Participants were primarily Black (65%) and heterosexual (82%). Over follow-up, 91 men acquired urethral Ng. Men with urethral US_NmUC had similar Ng risk to men with prior urethral Ng (adjusted hazard ratio [aHR]: 1.27; 95% CI: .65–2.48). Men with urethral US_NmUC had nonsignificantly increased Ng risk compared with men with urethral Ct (aHR: 1.51; 95% CI: .79–2.88), and significantly increased Ng risk compared with men without urethral Ng or Ct (aHR: 3.55; 95% CI: 1.27–9.91). Most of the protein antigens analyzed shared high sequence similarity. Conclusions: Urethral US_NmUC infection did not protect against gonorrhea despite substantial sequence similarities in shared protein antigens. Abstract : Cross-protective immunity between the gonococcus and the meningococcus may inform gonococcal vaccine development. In this study, we demonstrate that natural mucosal infection with a urethrotropic meningococcal clade does not protect against gonorrhea despite high sequence similarity in shared protein antigens.